Desain Riset Media Pembelajaran Augmented Reality Berbasis Discovery pada Mata Pelajaran IPA - Wisnu Pamungkas (Jurnal Pendidikan, 2023)
Abstract: Books are the media most often used by teachers. From the analysis of the teacher's needs, it is known that the teacher finds it difficult to explain to students about the form or describe the original form and sometimes gets stuck in just memorizing terms. Therefore, media is needed that can help teachers and students in the learning process. This research aimed to determine product specifications, attractiveness, and practicality of augmented reality learning media products in discovery learning activities in grade VIII natural science subjects on the human respiratory system at SMPK PENABUR Depok. This type of research is development research. The procedure in this development research was adapted from Borg & Gall. The subjects in this study were 40 grade VIII students of SMPK PENABUR Depok for the 2021/2022 academic year. In addition, this study also involved three experts in the fields of augmented reality, learning, and science education. Data analysis shows that the level of product attractiveness is 86.06% and the product practicality level is 88.64%. With these results, the product is declared feasible and can be used as a new learning media in the subject of the respiratory system in humans. Keywords: augmented reality, discovery, learning media.  Abstrak: Buku adalah media yang paling sering digunakan guru. Dari analisis kebutuhan guru diketahui bahwa guru kesulitan untuk menjelaskan kepada siswa mengenai bentuk atau menggambarkan wujud asli dan terkadang terjebak dalam kegiatan menghafal istilah saja. Oleh sebab itu, dibutuhkan media yang mampu membantu guru dan siswa dalam proses pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui spesifikasi produk, kemenarikan dan kepraktisan produk media pembelajaran augmented reality pada aktivitas pembelajaran discovery dalam mata pelajaran Ilmu Pengetahuan Alam (IPA) kelas VIII materi sistem pernapasan pada manusia di SMPK PENABUR Depok. Jenis penelitian ini merupakan penelitian pengembangan. Prosedur dalam penelitian pengembangan ini diadaptasi dari Borg & Gall. Subjek dalam penelitian ini siswa kelas VIII SMPK PENABUR Depok tahun ajaran 2021/2022 yang berjumlah 40 orang selain itu penelitian ini juga melibatkan tiga ahli pada bidang augmented reality, pembelajaran, dan pendidikan IPA. Hasil dari penelitian ini menunjukkan bahwa tingkat kemenarikan produk sebesar 86,06% dan tingkat kepraktisan produk sebesar 88,64%. Dengan hasil ini maka produk dinyatakan layak dan dapat dijadikan media pembelajaran yang baru dalam materi sistem pernapasan pada manusia. Kata Kunci: augmented reality, discovery, media pembelajaran.